The N terminus of the human alpha(1D)-adrenergic receptor prevents cell surface expression - Hague, C.; Chen, Z. J.; Pupo, A. S.; Schulte, N. A.; Toews, M. L.; Minneman, K. P. (Amer Soc Pharmacology Experimental Therapeutics, 2004)
We previously reported that truncation of the N-terminal 79 amino acids of alpha(1D)-adrenoceptors (Delta(1-79)alpha(1D)-ARs) greatly increases binding site density. In this study, we determined whether this effect was associated with changes in alpha(1D)-AR subcellular localization. Confocal imaging of green fluorescent protein (GFP)-tagged receptors and sucrose density gradient fractionation suggested that full-length alpha(1D)-ARs were found primarily in intracellular compartments, whereas Delta(1-79)alpha(1D)-ARs were translocated to the plasma membrane. This resulted in a 3- to 4-fold increase in intrinsic activity for stimulation of inositol phosphate formation by norepinephrine. We determined whether this effect was transplantable by creating N-terminal chimeras of alpha(1)-ARs containing the body of one subtype and the N terminus of another (alpha(1A) NT-D, alpha(1B) NT-D, alpha(1D) NT-A, and alpha(1D)NT-B). When expressed in human embryonic kidney 293 cells, radioligand binding revealed that binding densities of alpha(1A)- or alpha(1B)-ARs containing the alpha(1D)-N terminus decreased by 86 to 93%, whereas substitution of alpha(1A)- or alpha(1B)-N termini increased alpha(1D)-AR binding site density by 2- to 3-fold. Confocal microscopy showed that GFP-tagged alpha(1D)NT-B-ARs were found only on the cell surface, whereas GFP-tagged alpha(1B)NT-D-ARs were completely intracellular. Radioligand binding and confocal imaging of GFP-tagged alpha(1D)- and Delta(1-79)alpha(1D)-ARs expressed in rat aortic smooth muscle cells produced similar results, suggesting these effects are generalizable to cell types that endogenously express alpha(1D)-ARs. These findings demonstrate that the N-terminal region of alpha(1D)-ARs contain a transplantable signal that is critical for regulating formation of functional bindings, through regulating cellular localization.